2018
DOI: 10.1016/j.whi.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

“I Just Don't Know”: An Exploration of Women's Ambivalence about a New Pregnancy

Abstract: This study improves on previous findings that focus only on ambivalence related to pregnancy intention or to decision making, and explores women's mixed, fluctuating, or unresolved feelings and attitudes about pregnancy before many participants had completed pregnancy decision making. Acknowledging and exploring sources of ambivalence regarding pregnancy may help health providers and policymakers to comprehensively support women with respect to both their experiences and reproductive goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 40 publications
1
30
0
1
Order By: Relevance
“…Our findings are consistent with previous research reporting increased odds of depression (defined as a major EDS score of 10 or higher, by selected characteristics, and unadjusted and adjusted odds ratios (and 95% confidence intervals) respondents with a low social support score (MKSSI≤3.2), by selected characteristics, and unadjusted and adjusted odds ratios (and 95% confidence intervals) depressive episode) among women with an unplanned or poorly timed pregnancy. 19 Further, we assessed "ambivalence"-identified as a distinct and important category within patient-centered pregnancy perspectives 42,43 -and demonstrated that women reporting ambivalence had increased odds of depression. This finding supports consideration of multiple pregnancy perspectives that include ambivalence, rather than relying on strictly dichotomous outcomes (i.e., planned versus unplanned).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with previous research reporting increased odds of depression (defined as a major EDS score of 10 or higher, by selected characteristics, and unadjusted and adjusted odds ratios (and 95% confidence intervals) respondents with a low social support score (MKSSI≤3.2), by selected characteristics, and unadjusted and adjusted odds ratios (and 95% confidence intervals) depressive episode) among women with an unplanned or poorly timed pregnancy. 19 Further, we assessed "ambivalence"-identified as a distinct and important category within patient-centered pregnancy perspectives 42,43 -and demonstrated that women reporting ambivalence had increased odds of depression. This finding supports consideration of multiple pregnancy perspectives that include ambivalence, rather than relying on strictly dichotomous outcomes (i.e., planned versus unplanned).…”
Section: Discussionmentioning
confidence: 99%
“…Sources of uncertainty include previous experience with fertility and pregnancy, maternal‐foetal health, and the dynamics of the current family. Women are also concerned about the way pregnancy could influence their lives, goals, and dreams . Furthermore, this ambivalence is associated with poor pregnancy outcomes, such as an increased likelihood of premature membrane rupture, preterm delivery, and delivering a low birthweight infant .…”
Section: Discussionmentioning
confidence: 99%
“…Women are also concerned about the way pregnancy could influence their lives, goals, and dreams. 16 Furthermore, this ambivalence is associated with poor pregnancy outcomes, such as an increased likelihood of premature membrane rupture, preterm delivery, and delivering a low birthweight infant. 17 In the current study, the proportions of women who were in the third decade of their lives had average educational levels, and the proportions of women who were married indicated that ambivalence could have been involved in their decision to undergo an abortion.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was too small in these categories to enable us to carry out statistical analyses of their characteristics and behaviors. Ambivalence and uncertainty are important components of fertility decision-making (Aiken et al, 2016; Bernardi, Mynarska, & Rossier, 2015; Cutler et al, 2018) and are areas for continued research. Relatedly, we found that much of the literature on fertility preferences is atheoretical.…”
Section: Discussionmentioning
confidence: 99%